Microwave-assisted synthesis of polylactic acid-diol for polyurethane as biodegradable packaging material - Mirghani, Mohamed Elwathig Saeed; Ali, Fathilah; Razali, N I M; Ismail, T N M T Ismail; Omar, M Firdaus (IOP Science, 2021)
Since its discovery, plastic has been a part of human life and is widely employed in our daily lives. Excessive use of plastic has raised pollution rates around the world, with plastic ending up in landfills or the sea, posing a threat to both terrestrial and aquatic life. Considering this problem, the widespread use of polyurethanes (PUs) in many industries has resulted in unavoidable PUs pollution in everyday life. A reaction involving prepolymer, isocyanate, and polyol can be used to make PUs. Petroleum-based polyol and vegetable oil-based polyol are the two types of polyols available. Isocyanate will become the hard domain of the polymer in the PUs polymer chain, while polyol will become the soft domain. Polylactic acid-diol is the prepolymer used to make PU (PLA-diol). PLA-diol was previously made using a traditional heating approach, which takes a long time. To overcome this traditional method, microwave-assisted synthesis is proposed to synthesize the PLA-diol. The synthesis process involved synthesizing PLA-diol at different microwave power (450W – 900W) and at different reaction times (1 hour – 2 hours). The peak of the hydroxyl group in synthesized PLA-diol was characterized via the Fourier Transform Infrared Spectroscopy (FTIR) characterization to determine the functional groups of PLA-diol and gel permeation chromatography (GPC) characterization was done to determine the molecular weight of PLA-diol. The resulting PLA-diol will then be used to synthesis biodegradable PUs in the subsequence study.